Growth and Yield Characters of Two Cashew (Anacardium occidentale L.) Cultivars at Different Ages in Baubau City, South-East Sulawesi Province - Aliyaman Aliyaman; Didik Indradewa (Jurnal Ilmu Pertanian, 2019)
Baubau City is one of the cashew (Anarcadium occidentale L.) producer area in Southeast Sulawesi with area of 820 ha. This large area of cashew cultivation was not compensated with the productivity caused of low production. An effort to overcome this problem is identifying the growth and yield characters of cashew to apply the good agricultural practices for cashew plantation. The objective of this research was to determine the growth and yield of two cashew varieties at different tree ages; and to identify the relationship between the characters and the productivity of cashew trees in Baubau City. This research was arranged by oversite design with 2 varieties (the cashew with red pseudo-fruit and the cashew with yellow pseudo-fruit), 4 ages of cashew plant (5 years old, 17 years old, 26 years old, 37 years old) and 5 replications. The results showed that both varieties had no significantly different on growth and yield characters. At 37 years old, cashew trees still demonstrated the increasing of the productivity due to the increasing of growth and yield component i.e. plant biomass, the number of flower, the number of cashew nut per plant and cashew nut weight per kernel.